A Comparative Study of BSE 100 ESG index and BSE 100 index - Kumar R, Ganesh; Nimo J R, Ashlin (International Journal of Engineering and Technology, 2018)
To protect the well-being of people, sustainability in businesses is essential. Any step taken should protect the interests in all three spheres economic, social and ecological. Such a step is required today as there is a need to protect our resources for our future generations. The United Nations has taken several constructive steps towards sustainability. Now, these are being reflected in the businesses as well. As a result, several stock market indices have come into existence to meet these objectives. This paper studies the BSE 100 and BSE 100 ESG indices and provides results.Â Â